Pattern of ABO and Rhesus(Rh) Blood Group Among Blood Donors (TAJ: Journal of Teachers Association, 2009)
This study was carried out among the blood donors attending the Blood TransfusionDepartment of Khulna Medical College Hospital. Both ABO and Rhesus (Rh) blood grouping wasdone to see the pattern of ABO and Rh blood group among them. Maximum blood donors werebetween age group 18-37 years. Among the donors maximum were male 12105 (94.73%). Male:female ratio was 18:1. Among them B+ve was found 4286 (33.54%), B-ve was 127 (5.0%), O+vewas 4091 (32.02%), O-ve was 131 (1.03%), A+ve was 3014 (23.59%), A-ve was 74 (0.58%), AB+vewas 1019 (7.98%), AB-ve was 37 (0.29%). Overall total Rh positive blood group were 12410(97.11%) and total negative blood group were 369 (2.89%).doi: 10.3329/taj.v15i2.3910TAJ December 2002; Vol.15(2): 68-70